RISIKO SISTEMATIS, UKURAN PERUSAHAAN, CORPORATE GOVERNANCE, LEVERAGE DAN KEBIJAKAN DIVIDEN - Hesty Juni Tambuati Subing; gusni . (UPT Penerbitan Universitas Jember)
This research was conducted to obtain empirical evidence about the effect of variable Systematic Risk, Company Size, Leverage and Corporate Governance (Institutional Ownership, Number of Board of Directors, Total BOC), the dividend policy of the company. This study uses secondary data, such as financial reports, annual reports, and other related information from companies in the manufacturing industry listed in Indonesia Stock Exchange with the number of samples taken at 45 companies in the period 2012-2013. The sampling technique used was purposive sampling method. Panel data regression analysis is used. This study shows that company size has a positive and significant impact on the company's Dividend Policy, Leverage and Total's Board of Directors has a negative and significant impact on Dividend Policy. Other variables used in this study (Systematic Risk, Institutional Ownership and Number BOC) had no effect on dividend policy of companies in the manufacturing industry listed in Indonesia Stock Exchange during the period 2012-2013.